Effect of oleophilicity on Pistia inspired surface roughness / Najibah.A.Latif ... [et al.] - A.Latif, Najibah; S., Kasolang; Ahmad, M.A; A.Bakar, M.A (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Comprehensive application in nanostructured and advanced design bring science communities great interest towards these materials design. Biomimetic field is one of interests that allows scientist or researchers to take idea from nature and imitate it into numerous technology of structures, products and devices. Pistia stratiotes for example has intrinsic oleophilicity which rarely discovered. An investigation into pistia leaf inspired surface roughness for oleophilicity behaviour is studied. Four different nanocomposites materials with different nanofillers epoxy resin-based were successfully fabricated namely are epoxy polymer, graphene-filled, multiwall carbon nanotube (MWCNT)-filled and nanoclay-filled. Dinolite digital microscope was used to observe middle pistia inspired surfaces of the substrates and the surface roughness of the substrates had been measured using Alicona non-contact profilometer.